Digital signal processing with examples in MATLAB - Stearns, Samuel D. (Electrical engineering & applied signal processing series, 2011)
"This book explains the fundamentals of digital signal processing and how to apply DSP to the design of signal processing systems. Using the book perations, including spectral analysis and modeling. This second edition features new sections on simulation of continuous systems, the Chirp-z transform, linear and logarithmic sampling and resampling, the discrete sine transform, spread-spectrum techniques, digital differentiation, and integration. It also includes more information on the power density spectrum, implementation of the FFT, and the equation error method in adaptive signal processing"